2023
DOI: 10.1021/jacs.2c08816
|View full text |Cite
|
Sign up to set email alerts
|

The Myxobacterial Antibiotic Myxovalargin: Biosynthesis, Structural Revision, Total Synthesis, and Molecular Characterization of Ribosomal Inhibition

Abstract: Resistance of bacterial pathogens against antibiotics is declared by WHO as a major global health threat. As novel antibacterial agents are urgently needed, we re-assessed the broad-spectrum myxobacterial antibiotic myxovalargin and found it to be extremely potent against Mycobacterium tuberculosis. To ensure compound supply for further development, we studied myxovalargin biosynthesis in detail enabling production via fermentation of a native producer. Feeding experiments as well as functional genomics analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…17 NRPs possess other dhAA residues with great structural diversity, for example, Z-dehydrotryptophan (Z-DTrp) in telomycin 27 found in a Streptomyces strain; 73 Z-dehydroarginine (Z-DArg) in odilorhabdin 28 isolated from the nematode-symbiotic bacterium Xenorhabdus nematophila; 74,75 Z-b-ureidodehydroalanine in viomycin 29 (ref. 76) and aziridino[1,2-a]pyrrolidine in antitumour antibiotic azinomycins 30, produced by the culture broth of Streptomyces species; 77 O-aryl-N-methyl-Dtyrosine and E-2-amino-3-hydroxymethyl-4,5-epoxy-a,b-dehydropentanoic acid residues in dityromycin 31; 78 DVal in myxovalargin A 32 from Myxococcus fulvus strain Mx f65; 79 and an N-methyl-Z-dehydrophenylalanine residue (N-methyl-Z-DPhe) in tentoxin 33, a phytotoxic metabolite of the pathogenic fungus Alternaria tenuis 80 (Fig. 10).…”
Section: Reviewmentioning
confidence: 99%
“…17 NRPs possess other dhAA residues with great structural diversity, for example, Z-dehydrotryptophan (Z-DTrp) in telomycin 27 found in a Streptomyces strain; 73 Z-dehydroarginine (Z-DArg) in odilorhabdin 28 isolated from the nematode-symbiotic bacterium Xenorhabdus nematophila; 74,75 Z-b-ureidodehydroalanine in viomycin 29 (ref. 76) and aziridino[1,2-a]pyrrolidine in antitumour antibiotic azinomycins 30, produced by the culture broth of Streptomyces species; 77 O-aryl-N-methyl-Dtyrosine and E-2-amino-3-hydroxymethyl-4,5-epoxy-a,b-dehydropentanoic acid residues in dityromycin 31; 78 DVal in myxovalargin A 32 from Myxococcus fulvus strain Mx f65; 79 and an N-methyl-Z-dehydrophenylalanine residue (N-methyl-Z-DPhe) in tentoxin 33, a phytotoxic metabolite of the pathogenic fungus Alternaria tenuis 80 (Fig. 10).…”
Section: Reviewmentioning
confidence: 99%
“…This mode-of-action study sets the stage for future structure-based structural improvement to overcome the disadvantages of myxovalargins, including compound availability and narrow therapeutic index. 138 Surup and co-workers discovered two cyclic depsipeptides termed crocadepsins A (74) and B (75) from the myxobacterium Chondromyces crocatus Cm c5 by integrating genome mining and comparative metabolomics approaches. 139 These compounds feature cinnamoyl, dehydrobutyrine, chlorination, b-hydroxy-g-amino acid residue, and 3-methyl ornithine moieties, respectively.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…135–137 Very recently, Koller and co-workers revised the l -configuration at the Val 10 residue that was previously misassigned the d stereochemistry. 138 They reassessed the antimicrobial spectrum of 73 and found that it exhibited potent antitubercular activity with an MIC of 0.2 μg mL −1 in addition to other pathogens. Compound 73 demonstrated in vivo efficacy in a mouse model of acute M. tuberculosis infection and displayed good pharmacokinetic properties with no adverse effects, opening up a potential therapeutic window for application.…”
Section: Systematic Summarization Of New Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This plethora of natural products holds the promise of hidden bioactivities against often under-screened pathogens. Considering myxobacterial natural products, this is displayed by the recent findings of chondramides active against SARS-CoV-2 ( 14 ), the antitubercular properties of myxovalargin ( 15 ), or the potent anti-filarial activity of corallopyronin A through the inhibition of Wolbachia endosymbionts ( 16 ). Moreover, evaluation of the biosynthesis can be used to improve production titers in the heterologous expression of a natural product, as displayed for corallopyronin A ( 17 ), or to heterologously produce improved derivatives of a natural product family, as displayed for disorazoles ( 18 ).…”
Section: Introductionmentioning
confidence: 99%